Entrepreneurship in international marketing - Zou, Shaoming; Xu, Hui.; Shi, Linda Hui. (Bingley, U.K. : Emerald, 2015)
The latest volume in the Advances in international marketing series is a fresh addition to the international marketing literature, expanding the current knowledge in several significant ways. Divided in to two sections, the first part of Vol. 25 addresses important issues concerning entrepreneurship in the international market. Pulling together papers authored by well-known scholars they look at issues such as born-global firms evolution, market orientation, alliance capabilities, customer orientation, and performance in the global market. Collectively, these papers shed significant new light on the role of entrepreneurship in born-global firms and exporting firms. The second part of Entrepreneurship in International Marketing brings together a collection of papers dealing with contemporary international marketing issues, including the conceptual domain of international marketing, global brands and luxury brands in emerging markets, international retail supply chains, and exit behaviour of FDI firms.
Born-global firms : evolution of a contemporary phenomenon / Gary Knight -- The market orientation of domestic and international new ventures / Tage Koed Madsen, Hans Eibe Sørensen, Rosalina Torres-Ortega -- The effects of entrepreneurial marketing strategies on the long-term competitive sustenance of born global firms : examples from the Indian knowledge-intensive services industry / Nishant Kumar, Ali Yakhlef -- The alliance capability of technology-based born globals / Liliya Altshuler Oxtorp, Ulf Elg -- The effect of dynamic capabilities on value-based pricing and export performance / Katharina Maria Hofer, Lisa Maria Niehoff, Gerhard A. Wuehrer -- Export marketing strategy and performance among micro and small Brazilian enterprises / Reynaldo Dannecker Cunha, Thelma Valeria Rocha -- The effect of social media adoption on exporting firms performance / María del Carmen Alarcón, Alex Rialp, Josep Rialp -- A literature review, classification and simple meta-analysis on the conceptual domain of international marketing : 1990-2012 / Sudhir Rana, Somesh Kr. Sharma -- A framework for understanding firms' foreign exit behavior / Qun Tan, Carlos M.P. Sousa -- Institutional forces and firms' positioning in China and Brazil / Ulf Elg, Pervez Ghauri -- Does the value of global brands apply to both foreign and domestic-based global brands? / Stanford A. Westjohn, Peter Magnusson, Joyce X. Zhou -- Luxury brands in emerging markets : a case study on China / Annie Peng Cui, Theresa A. Wajda, Michael F. Walsh -- The effects of stability, diversity, and density on relationship flexibility in an international retail supply network : a proposed theory and research hypotheses / Jack Cadeaux.
Print version record
Keywords: Business & Economics -- International -- Marketing; International business; Business & management; Export marketing; Entrepreneurship